2014
DOI: 10.1177/1367006913515769
|View full text |Cite
|
Sign up to set email alerts
|

Referential context effects in non-native relative clause ambiguity resolution

Abstract: We report the results from two experiments investigating how referential context information affects native and non-native readers’ interpretation of ambiguous relative clauses in sentences such as The journalist interviewed the assistant of the inspector who was looking very serious. The preceding discourse context was manipulated such that it provided two potential referents for either the first ( the assistant) or the second ( the inspector) of the two noun phrases that could potentially host the relative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Thus, there was a lesser conflict between syntactic and lexical cues in the embedded conditions and L2 speakers behaved similarly to native speakers. This explanation is in line with research on L2 ambiguity resolution, which has found that L2 speakers prioritize lexico-semantic and pragmatic cues over structural cues to resolve different types of lexical and structural attachment ambiguities (Juffs, 1998;Juffs & Harrington, 1996;Felser et al, 2003;Pan & Felser, 2011;Pan, Schimke & Felser, 2015;Papadopoulou & Clahsen, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, there was a lesser conflict between syntactic and lexical cues in the embedded conditions and L2 speakers behaved similarly to native speakers. This explanation is in line with research on L2 ambiguity resolution, which has found that L2 speakers prioritize lexico-semantic and pragmatic cues over structural cues to resolve different types of lexical and structural attachment ambiguities (Juffs, 1998;Juffs & Harrington, 1996;Felser et al, 2003;Pan & Felser, 2011;Pan, Schimke & Felser, 2015;Papadopoulou & Clahsen, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, learners of different L1s would pattern together showing L2‐specific processing profiles rather than L1 influence during online processing. Potential L1 influence would be restricted to behavior in offline tasks (Clahsen & Felser, ; Pan et al., ; Roberts et al., ). However, studies have also documented the reverse finding, with L1 effects surfacing during online processing but not in offline tasks (Hopp, ; Roberts & Liszka, ).…”
Section: Introductionmentioning
confidence: 99%
“…One crucial factor is the level of linguistic analysis at which L1 influence is investigated. While there is abundant evidence of L1 effects in phonetics and phonology (e.g., Flege, Munro, & MacKay, 1995;Hanulikova, Mitterer, & McQueen, 2011) and with respect to the lexicon (e.g., Dijkstra & van Heuven, 2002), there are mixed findings when it comes to morphosyntactic and discourse-level phenomena (Clahsen & Felser, 2006;Hopp, 2010;Pan, Schimke, & Felser, 2015). The fact that L1 influence seems to be more elusive in these domains can, in turn, be related to at least two potential factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case, similar terminology refers to a bias for discourse-biased interpretations of globally ambiguous NP attachment ambiguities (Pan, Schimke & Felser, 2015), i.e., favor the syntactic attachment that yields an interpretation that better fits the discourse. It is hard to imagine this bias in terms of retrieval cues.…”
mentioning
confidence: 99%